HUBUNGAN ANTARA LINGKUNGAN SOSIAL DENGAN MOTIVASI BELAJAR SANTRI DI PESANTREN MADINATUL ILMI ISLAMIYAH - Nelpa Fitri Yuliani (Universitas Negeri Padang, 2013)
The background of this research is based on the lack of students motivation in learning. The lack of student motivation can influenced many factor, one of them is social environment of pesantren. The social environment of pesantren is a real relationship between humans, interaction between learners and educators with other people who are involved in the interaction of education in schools. The social environment can affect students' learning motivation in the pesantren. The aim of this study is to describe the social environment of pesantren, describing the students' learning motivation and the relationship between the social environments to motivate students to learn in pesantren. This research is quantitative correlation type with 28 research subjects students are studying in pesantren Madinatul Ilmi Islamiyah. The results of this study can showing that there is a significant relationship between social environment of pesantren with student’s learning motivation.